Optimizing the production of Polyphosphate from Acinetobacter towneri - J. Aravind; T. Saranya; P. Kanmani (Global Journal of Environmental Science and Management)
Inorganic polyphosphates (PolyP) are linear polymers of few to several hundred orthophosphate residues, linked by energy-rich phosphoanhydride bonds. Four isolates had been screened from soil sample. By MALDI-TOF analysis, they were identified as Bacillius cereus, Acinetobacter towneri, B. megaterium and B. cereus. The production of PolyP in four isolates was studied in phosphate uptake medium and sulfur deficient medium at pH 7. These organisms had shown significant production of PolyP after 22h of incubation. PolyP was extracted from the cells using alkaline lysis method. Among those isolates, Acinetobacter towneri was found to have high (24.57% w/w as P) accumulation of PolyP in sulfur deficient medium. The media optimization for sulfur deficiency was carried out using Response surface methodology (RSM). It was proven that increase in phosphate level in the presence of glucose, under sulfur limiting condition, enhanced the phosphate accumulation by Acinetobacter towneri and these condition can be simulated for the effective removal of phosphate from wastewater sources.